Infographic Development through Instagram to Reduce Mathematics Anxiety and Increase Student Learning Outcomes - Sari, Arika; Octaria, Dina; Utari, Rahma Siska; Somakim, Somakim; Hiltrimartin, Cecil; Hartono, Yusuf; Darmawijoyo, Darmawijoyo (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Research is a descriptive research that aims to describe the product development process in the form of infographic learning media in algebra material through Instagram that is appropriate for students to use for independent learning activities. This research focuses on creating infographic media in algebra material through Instagram to reduce mathematics anxiety and improve learning outcomes. The method used in this research is development research using the Sadiman’s model. The stages in this development model are preliminary stage, prototyping stage, and final stage, which from three stages contain of nine steps, namely identification of needs, formulation of objectives, formulation of materials, formulation of success measurement tools, writing of media scripts, production, tests/trials, revisions and the final product. There were 34 students of seventh graders of junior high school participating in this study. Data was collected through interviews, observations, tests, and questionnaires. Data were analyzed quantitatively and qualitatively. The results of the validation test by experts show that 93% of infographics through Instagram as strengthening students' understanding are included in the valid category and are suitable for use in the learning process. In addition, as many as 88% of students experienced an increase in learning outcomes after learning to use infographics through Instagram which indicated that the level of student anxiety in learning mathematics had decreased.